An Assessment of the Intestinal Lumen as a Site for Intervention in Reducing Body Burdens of Organochlorine Compounds - Ronald J. Jandacek; Stephen J. Genuis (The Scientific World Journal)
Many individuals maintain a persistent body burden of organochlorine compounds (OCs) as well as other lipophilic compounds, largely as a result of airborne and dietary exposures. Ingested OCs are typically absorbed from the small intestine along with dietary lipids. Once in the body, stored OCs can mobilize from adipose tissue storage sites and, along with circulating OCs, are delivered into the small intestine via hepatic processing and biliary transport. Retained OCs are also transported into both the large and small intestinal lumen via non-biliary mechanisms involving both secretion and desquamation from enterocytes. OCs and some other toxicants can be reabsorbed from the intestine, however, they take part in enterohepatic circulation(EHC). While dietary fat facilitates the absorption of OCs from the small intestine, it has little effect on OCs within the large intestine. Non-absorbable dietary fats and fat absorption inhibitors, however, can reduce the re-absorption of OCs and other lipophiles involved in EHC and may enhance the secretion of these compounds into the large intestine—thereby hastening their elimination. Clinical studies are currently underway to determine the efficacy of using non-absorbable fats and inhibitors of fat absorption in facilitating the elimination of persistent body burdens of OCs and other lipophilic human contaminants.